DYNAMICS OF INDICATORS OF CADETS’ MORPHOLOGICAL AND FUNCTIONAL DEVELOPMENT IN THE PROCESS OF THEIR PHYSICAL EXERCISES OF DIFFERENT ORIENTATION - Holovanova, I.A.; Prontenko, K.V.; Lyakhova, N.A.; Romanchenko, D.Yu.; Stoianov, R.V.; Honcharuk, A.V.; Sydorchuk, V.V. (World of Medicine and Biology, 2024)
The article aimed to investigate the dynamics of indicators of cadets’ morphological and functional development in the process of practicing various military-applied sports during their academic training. The research involved 218 male cadets aged 17-23 years who were engaged in various military-applied sports (n = 188) and who were not additionally engaged in sports (n = 30) during their academic training. Cadets’ morphological and functional development was assessed by the following indicators: body mass index, vital index, strength index, and the Robinson index, results in 100 m run, pull-ups, and 3 km run. It was found that military-applied sports have a more efficient impact on the indicators of cadets’ morphological and functional development compared to the traditional method of physical training. Depending on the orientation of physical exercises that underlie the sport, each has one or another pronounced impact. Thus, the improvement of the cardiovascular and respiratory systems, as well as the development of endurance are more effectively influenced by military pentathlon and orienteering; the improvement of the muscular system and the development of strength qualities – by kettlebell lifting and powerlifting; the development of speed and agility – by hand-to-hand combat and sports games. A high level of cadets’ morphological and functional development will ensure the formation of their physical readiness for future professional and combat activities and will contribute to the performance of assigned tasks.